Design and evaluation of multi-floor LoRaWAN system for indoor deployment - Idris, Fakrulradzi; Maniaruse, Dakshayanie; Hashim, Norlezah; Abdul Latiff, Anas (Research and Scientific Innovation Society, 2025)
This study explores the impact of gateway placement on the performance of LoRaWAN networks in a multi floor indoor environment, focusing on signal propagation and packet delivery reliability. Leveraging The Things Network (TTN) as the network server and Ubidots for real-time data visualization, the project involved designing and deploying an indoor LoRaWAN setup to evaluate how gateway elevation influences key metrics such as Received Signal Strength Indicator (RSSI), Signal-to-Noise Ratio (SNR), and Packet Delivery Ratio (PDR). Results indicate that while Level 4 gateway placement offers stronger performance in line- of-sight (LOS) areas, it suffers from sharp degradation in lower floors. Conversely, Level 3 gateway placement provides more consistent coverage, particularly in non-line-of-sight (NLOS) and in the first floor areas. These findings emphasize that optimal gateway placement is not necessarily the highest point, but rather a strategically balanced position suited to the building’s structure. The integration of TTN and Ubidots proved essential for reliable network management, supporting practical recommendations for scalable and energy efficient LoRaWAN deployments in complex indoor environments.